2007
DOI: 10.1002/pola.22196
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silicon‐bridged polythiophene derivatives and their applications to EL device materials

Abstract: Oxidative homo-coupling of 2,6-bis(tributylstannyl)dithienosiloles afforded poly(dithienosilole-2,6-diyl)s as novel polythiophene derivatives with intrachain silicon bridges, which exhibited red-shifted UV absorption maxima, as compared with those of silole-free polythiophenes.Alternate copolymers also were prepared by cross-coupling reactions of 2,6dibromodithienosiloles with distannylthiophene or bithophene. Applications of the resulting polymers to electroluminescence devices and a field effect transistor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…The absorption maxima were blue-shifted from those reported for DTS homopolymers (pDTS, l max ¼ 533-561 nm), 22,23 DTS-bithiophene alternate polymers (pDTS2T, 544-558 nm) 22,23 and a DTS-pyridinothiadiazole alternate polymer (pDTSPTA, 732 nm) 20 (Scheme 4). The introduction of pyridine units into pDTS2T and pDTS appeared to hinder the planarity of the resulting p-conjugated systems due to steric repulsion between the C-H bonds of the adjacent thiophene and pyridine rings.…”
Section: Optical Propertiesmentioning
confidence: 75%
“…The absorption maxima were blue-shifted from those reported for DTS homopolymers (pDTS, l max ¼ 533-561 nm), 22,23 DTS-bithiophene alternate polymers (pDTS2T, 544-558 nm) 22,23 and a DTS-pyridinothiadiazole alternate polymer (pDTSPTA, 732 nm) 20 (Scheme 4). The introduction of pyridine units into pDTS2T and pDTS appeared to hinder the planarity of the resulting p-conjugated systems due to steric repulsion between the C-H bonds of the adjacent thiophene and pyridine rings.…”
Section: Optical Propertiesmentioning
confidence: 75%
“…Monomer DTS-Sn was prepared as reported in the literature. 5 GPC analysis of the polymers was performed with Shodex columns, KF804 and KF806 connected in series, using a UV detector (240 nm). NMR spectra were measured on a JEOL model LA-400 spectrometer.…”
Section: General Proceduresmentioning
confidence: 99%
“…For example, UV absorption maximum of poly [4,4-bis(4-butylphenyl)dithienosilole-2, 6-diyl] appears at 561 nm, red-shifted from that of regio-regular poly(3-hexylthiophene) (HT > 95%), by about 100 nm. It was also demonstrated that DTS-thiophene and bithiophene copolymers could be used as hole-transport emitters for OLEDs 5 and p-type semiconductors. 7 DTS-fluorene 8,9 and DTS-dithienylenebenzothiadiazole 6 copolymers were also synthesized recently, as photoluminescence and photovoltaic-active materials, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] Recently, the charge-carrier mobility and stability of solution-processable organic semiconductors have sharply improved, enabling the achievement of thin-film-transistor (TFT) performances as high as those of vacuum-deposited oligomers. [9][10][11][12] To obtain a high mobility, the charge carriers must be transported through the TFT channel with a minimum of trap states.…”
Section: Introductionmentioning
confidence: 99%